Marketing - William M. Pride; O. C. Ferrell (Boston, Massachusetts : Cengage, 2020)
Gain an understanding of today's marketing principles with Pride/Ferrell's engaging MARKETING. Develop the knowledge and decision-making skills to succeed as in-depth coverage highlights fundamental marketing concepts and strategies. Practical applications and examples emphasize the latest social networking, digital marketing, social and environmental responsibility, globalization, entrepreneurship and marketing during transition. This edition also expands coverage of business markets and buying behavior, marketing channels and supply-chain management, retailing, personal selling and marketing analytics. An eBook lets you highlight terms and includes embedded Concept Check quizzes to assess understanding of key concepts. You have convenient mobile access to assignments, digital flashcards, company videos, an interactive marketing plan, practice exams and activities as a marketer.
Keywords: Marketing; Textbooks